Analisis Spasial Degradasi Hutan dan Deforestasi: Studi Kasus di PT. Duta Maju Timber, Sumatera Barat - Mulyanto, Lukman; Jaya, I Nengah Surati (Jurnal Manajemen Hutan Tropika, 2004)
This study develops a predictive model on forest degradation and deforestation in Duta Maju Timber concession area West Sumatera during 1999 and 2002 period. The study found that the likelihoods of the forest degradation and deforestation are significantly affected respectively by distance from villages/settlement centers (X1), distance from rivers/streams (X3), distance from public road/logging roads (X2) and the age of logged over forest (X4). The probality of forest changes was negatively correlated with the distance from the villages and the age of logged over forest. While the rest variables (X3 and X2) are positively correlated. The best predictive model obtained for predicting forest degradation and deforestation was the logistic model (y =(10-7,64).X4-23,565.X1-6,889 . X35,505. X23,712) having considerably high coefficient correlation.